Behavioural Improvement of People with Autism Spectrum Disorder - Manuel Ojea Rúa; Andrea Vieira Vázquez (Language, Literature and Education: Research Updates Vol. 2, 2025)
People with Autism Spectrum Disorder (ASD) are defined by the International Classification of Mental Disorders. The basic aim of this study is to prove whether an integrated psycho-pedagogical program, structured in accordance with the psychosocial and educational mediation model, would lead to greater behavioural and educational action training in people with Autism Spectrum Disorder (ASD). The program has basically focused on psycho-cyto-cognitive mediation criteria, based on the progressive creation of neural networks and connections between information and acquired behaviours according to the particular needs of people with ASD selected according to the basic competencies initially assessed. An experimental research design on three measures has been based, on one pre-test (I), and two post-tests (II-III) was realized. A total of 14 children with ASD participated in the intervention program specific ad hoc applied for two years. Results found through comparative analysis Friedman Test and Multivariate Tests Within- Subjects Effects, showed that the intensive intervention improved children´s behaviour and their functional adaptation to the context and, in conclusion, social life and inclusion improved. More experiments and larger data sets will be needed however the indications are there that a collective learning environment needs to be created, therefore this is a very timely paper. This can be tested further. In conclusion, the integrated program can be considered an effective intervention to promote the development of social skills.